OPTIMALISASI PEMANFAATAN GEDUNG ANJUNG SENI IDRUS TINTIN DALAM PENGEMBANGAN WISATA DI KOTA PEKANBARU - Hayland Grace Mariata; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The using of Art Anjung Idrus Tintin Hall looked worst because the condition became worse day by day so, the Departement of Tourism and Economic Creative the Province of Riau continues to consider the need for a management agency to manage the Anjung of Idrus Tintin and they formed UPT. Bandar Serai under the direct supervision of the Departement of Tourism and Economic Creative the Province of Riau. The issues discussed in the thesis is described on the optimalitation of using Art Anjung Idrus Tintin in developing tourism sport in Pekanbaru. The purpose of this research is tu figure out how to optimalitation of using Art Anjung Idrus Tintin hall and the factors that effect the optimalitation of using Art Anjung Idrus Tintin hall in Developing tourism sport in Pekanbaru. The researcher used asset optimalitation theory by Siregar (2004) assumed it was the study process of management asset that divided by five levels like asset investation, legal audit, asset evaluation, asset optimalitation, at last audit and control. And the conclusion from the statements about that asset optimalitation was the optimalitation using from an asset that had more useful. Or increased income effectively. Because of that, the researcher applied descriptive qualitative method and collected the data by observation and interview the audience in this part. The result of this research showed that in optimalitation of Art Anjung Idrus Tintin Hall needed increasing asset from inside or outside part of this hall. Beside that increasing of human’s quality and copability needed to create master of plan that formed this hall became the most luxurious hall in Indonesia as international level and also can be icon of Pekanbaru.Keywords : Optimalitation, Management Asset, ASIT Hall in Pekanbaru